2018
DOI: 10.1007/978-3-319-76312-5_2
|View full text |Cite
|
Sign up to set email alerts
|

For Pragmatism and Politics: Crime, Social Harm and Zemiology

Abstract: What does it mean to go 'beyond criminology'? This chapter seeks to tease out some of the issues at stake in the relationships between critical criminology, social harm and zemiology. In so doing, I engage in both personal reflection as well as critical considerations of some of the responses to Beyond Criminology, and on these bases suggest that there are a number of theoretical differences between critical criminology, social harm, and zemiology. These, in turn, pertain to the question of whether zemiology s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 21 publications
0
21
0
1
Order By: Relevance
“…Beginning with Sutherland’s (1940, 1945, 1949) work on white-collar crime, criminologists have used a variety of strategies to go beyond the straitjacket of the legalistic definition of crime in order to examine the significant wrongdoings of corporations and states. Tombs (2018, p. 13) notes that he has used “a series of intellectual gymnastics” in seeking to legitimate inclusion of workplace death, injury, and illness within the field of criminology including use of crime to cover violations of noncriminal law, following Sutherland to include what is punished and what is punishable, making invisible crimes visible by relating their elements to “real crimes,” and questioning the assumptions underlying conceptions of “real crime” and reworking the assumptions to cover corporate violence. Likewise, some state crime scholars expand the legalistic definition of crime to include violations of international law (e.g., treaties, accords, U.N. Charter, humanitarian law; Kramer & Michalowski, 2005), forms of organizational deviance (Green & Ward, 2004), or social harms/injuries that cause outcomes that are analogous to those prohibited by criminal law (Michalowski, 2010).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Beginning with Sutherland’s (1940, 1945, 1949) work on white-collar crime, criminologists have used a variety of strategies to go beyond the straitjacket of the legalistic definition of crime in order to examine the significant wrongdoings of corporations and states. Tombs (2018, p. 13) notes that he has used “a series of intellectual gymnastics” in seeking to legitimate inclusion of workplace death, injury, and illness within the field of criminology including use of crime to cover violations of noncriminal law, following Sutherland to include what is punished and what is punishable, making invisible crimes visible by relating their elements to “real crimes,” and questioning the assumptions underlying conceptions of “real crime” and reworking the assumptions to cover corporate violence. Likewise, some state crime scholars expand the legalistic definition of crime to include violations of international law (e.g., treaties, accords, U.N. Charter, humanitarian law; Kramer & Michalowski, 2005), forms of organizational deviance (Green & Ward, 2004), or social harms/injuries that cause outcomes that are analogous to those prohibited by criminal law (Michalowski, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Figure 1 shows the precipitous increase in federal and private student loan debt from 2006 to the present (U.S. Board of Governors of the Federal Reserve System, 2020).…”
Section: Trends In Student Loan Debt and Social Harmmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition to rejecting the use of the term 'victim', children reported that they had a different view of harm. Rather than reflecting a more adult and legally aligned approach to offence/non-offence, the children evinced a greyer, more socially protean reality to harms which might have been done to them (see Tombs, 2018). Children did not see that certain harms or acts should or even could make them, in a conventional manner, 'victims' (c.f.…”
Section: Mediated Harm: Children's Differing Views Of Harmmentioning
confidence: 99%